Determine the Frequency, Causes and Outcomes of Neonates Admitted in Neonatal Intensive Care Unit - Sadaf Liaqat, Javaria Yonous, Sajid Hussain Sherazi, Ghulam Rasool, M. Yaqoob (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the frequency of admissions in neonatal intensive care unit and also find out the causes and outcomes of admitted neonates. Study Design: Cross-sectional study Place and Duration: Department of Paediatrics, Doctors Trust Hospital Sargodha from 15th January 2021 to 15th July 2021. Methodology: Five hundred and eighty neonates admitted in NICU during the study period with ages 0 to 28 days, were analyzed. Patient’s detailed demographics were recorded after taking written consent from parents/guardians. Causes of admission to NICU, outcomes in term of discharged and death were determined. Results: Four hundred and twenty (72.41%) neonates were male while 160 (27.59%) were females. Majority of neonates 325 (56.03%) were admitted during first seven days of life. Sepsis was the most common cause of admission found in 230 (39.66%) neonates followed by neonatal jaundice, birth asphyxia, prematurity with respiratory distress syndrome, pneumonia, congenital heart disease, IUGR and IDM in 145 (25%), 120 (20.69%), 38 (6.55%), 30 (5.17%), 5 (0.86%), 4 (0.69%) and 4 (0.69%) neonates respectively. Out of 580 neonates 40 (6.90%) neonates were died while 510 (87.93%) were discharged after complete recovery and 30 (5.17%) patients left against medical advice. Conclusion: Sepsis, neonatal jaundice and birth asphyxia were the most common causative factors for admissions to NICU. Mortality rate was also high among these patients. Keywords: Neonatal Intensive Care Unit, Sepsis, Neonatal Jaundice, Birth Asphyxia, Prematurity, Recovery, Mortality